BUDAYA BERBAHASA ASING DI SD LABORATORIUM UNIVERSITAS NEGERI MALANG KOTA BLITAR - Kholis, Nur (Al-Mudarris: Journal Of Education, 2018)
This study was intended, firstly, to know the foreign language culture at Elementary School of Laboratorium Universitas Negeri Malang in Blitar, and secondly, to analyze the factors that influence the foreign language culture there. This research was qualitative in nature with case study approach. The setting of the study was at Elementary School of Laboratorium Universitas Negeri Malang in Blitar. The objects of the study were the foreign language culture and its determinant factors, while the subjects were the principals, the vice principals, the teachers, and the students. The data were collected by administering in-depth interview, documentation and observation techniques. The validity of data was ensured by credibility, transferability, dependability, and confirmability checking techniques. The data were then analyzed in interrelated stages of data display, data reduction, conclusion drawing, and data verification. This study concludes that the foreign language culture at SD Laboratorium UM was developed through three stages of planning, implementation, and evaluation. The factors that influence the culture of foreign languages are the institutional management system/software, the English teacher quota, the learning model, and the learning infrastructure.